Distinct Functions of STARCH SYNTHASE 4 Domains in Starch Granule Formation . Issue 1 (13th November 2017) - Lu, Kuan-Jen; Pfister, Barbara; Jenny, Camilla; Eicke, Simona; Zeeman, Samuel C.
Abstract : In Arabidopsis leaves, the catalytic C-terminal region of STARCH SYNTHASE 4 promotes starch granule initiation while its noncatalytic N-terminal region determines starch granules morphology. Abstract: The formation of normal starch granules in Arabidopsis ( Arabidopsis thaliana ) leaf chloroplasts requires STARCH SYNTHASE 4 (SS4). In plants lacking SS4, chloroplasts typically produce only one round granule rather than multiple lenticular granules. The mechanisms by which SS4 determines granule number and morphology are not understood. The N-terminal region of SS4 is unique among SS isoforms and contains several long coiled-coil motifs, typically implicated in protein-protein interactions. The C-terminal region contains the catalytic glucosyltransferase domains, which are widely conserved in plant SS and bacterial glycogen synthase (GS) isoforms. We investigated the specific roles of the N- and C-terminal regions of SS4 by expressing truncated versions of SS4 and a fusion between the N-terminal region of SS4 and GS in the Arabidopsis ss4 mutant. Expression of the N-terminal region of SS4 alone did not alter the ss4 mutant phenotype. Expression of the C-terminal region of SS4 alone increased granule initiation but did not rescue their aberrant round morphology. Expression of a self-priming GS from Agrobacterium tumefaciens also increased the number of round granules. Remarkably, fusion of the N-terminal region of SS4 to A. tumefaciens GS restored the development of wild-type-like lenticular starch granules. Interestingly, the N-terminal region of SS4 alone or when fused to GS conferred a patchy subchloroplastic localization similar to that of the full-length SS4 protein. Considered together, these data suggest that, while the glucosyltransferase activity of SS4 is important for granule initiation, the N-terminal part of SS4 serves to establish the correct granule morphology by properly localizing this activity.